Discrepancy of eye injuries in mechanism, clinical features, and vision prognosis by different causative sports - Zhang, Ying; Jia, Hongzhen; Kang, Xin; Yang, Qinghua; Ying, Jun; Wu, Qiong; Zheng, Zhong; Zhang, Hongtao (Frontiers in Public Health, 2023)
Objective: To investigate the epidemiological and clinical characteristics of sports-related eye injuries in China, as well as how they differ depending on the sport or other specific factor that caused them. Methods: Consecutive medical records from 2015 to 2019 of sports-related eye injuries from a standardized database in nine tertiary referral hospitals in China were retrospectively reviewed and analyzed. Results: A total of 377 eyes in 376 inpatients (mean age, 22.5±7.3 years; men:women 15.4:1) were included. Soccer (46.8%), basketball (27.1%), and badminton (16.8%) were the top three sports that caused injury. Ball strikes (74.7%), physical collision (13.8%), and racket/equipment beating (9.0%) were the common specific causes of injury. Blunt force injuries (95.8%) and close globe injuries (95.1%) accounted for the majority of injuries. Open globe injuries occurred more in basketball (8.3%) than in other sports, mainly due to physical collision (12.8%) and racket/equipment beating (11.8%). Basketball (13.4%) or physical collision (21.3%) caused Zone I injuries more frequently than other sports. Soccer (60.5%) and basketball (54.6%) caused more injuries to the posterior segment of the eyeball than other sports, mainly due to ball strikes (96.6%). Badminton (69.8%) and racket beating (61.8%) caused more Zone II globe injuries than other sports. In badminton, the percentage of hyphema (85.7%), the most typical symptom of eye damage, and ultimate visual acuity (VA) ≥20/40 (88.9%) was the greatest. A final low vision score of (≤4/200) was observed in 10.6% of all participants, including three participants who had an eye removed due to rupturing. The final VA was positively correlated with the presenting VA (r=0.421). Conclusions: Sports can lead to high proportions of ocular contusion injury and low vision. VA prognosis is closely related to initial VA following ocular sports trauma, which is directly determined by the causative sports and/or the specific causes. Effective eye protection is imperative to avoid or reduce visual impairments of sports participants.